Anterior open bite and deleterious habits in preschool children from public schools - Valchia Gotardo Gusson Colombi; Rafael Celestino de Souza; Maria Helena Monteiro Barros Miotto; Isabela Floriano; Tamara Kerber Tedesco; Juan Sebastian Lara; Elisa Cristina Gnoatto; José Carlos Petorrossi Imparato (Associação Brasileira de Odontologia, 2017)
Objective: this study aims to evaluate the prevalence of anterior open bite and its association with deleterious oral habits, such as use of pacifier, finger-sucking habit and baby bottle in preschool children. Material and Methods: a cross-sectional study was carried out with 142 children, aged three to five years old, from 9 schools in the city of Nova Venécia, ES, Brazil. A properly calibrated examiner conducted the examination of occlusion under natural light and with the aid of medical examination stick. In addition, a semi-structured form with closed questions on deleterious oral habits in children was sent to parents/guardians. The sociodemographic, economic and anterior open bite data was verified through the Fisher exact test and the odds ratio values were calculated with 95% confidence interval. Results: it was found a prevalence of 31.69% (45) of anterior open bite. Moreover, 45.8% (65) of the children had a pacifier sucking habit, 14.8% (21) finger sucking habit and 73.9% (105) used baby bottle. Children with habit of pacifier sucking showed 5.58 (2.54-12.24) more likely to have anterior open bite than children without the habit. Preschool children with finger sucking habit showed 3.55 (1.37-9.21) more likely to have malocclusion. Children who used baby bottle presented 2.29 (1.06-4.97) more likely to have anterior open bite. Conclusion: high prevalence of anterior open bite is observed in the studied population and it is associated with the pacifier sucking habit, finger sucking habit and use of a baby bottle.